The lighting design of commercial establishments as a factor of consumerism - Cucueco, Armi May S.; Mayo, Adelaida Villaraza (1998.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Lighting, Architectural and decorative; Lighting -- Psychological aspects